Introvert doodles : an illustrated look at introvert life in an extrovert world. - Wilson, Maureen "Marzi," (Adams Media, 2016)
Whoever said there's strength in numbers lied. Meet Marzi. She's an introvert who often finds herself in awkward situations. Marzi used to feel strange about her introverted tendencies. Not anymore! Now she knows that there are tons of introverts out there just like her--introverts who enjoy peace and quiet, need time alone to recharge their battery, and who prefer staying in with their pet and a good book to awkward social interactions. Just like Marzi, these introverts can often be found in libraries, at home watching Netflix, brainstorming excuses to miss your next party, or doodling cute cartoons. Being an introvert in an extrovert world isn't always easy, but it certainly is an adventure. In Introvert Doodles, follow Marzi through all of her most uncomfortable, charming, honest, and hilarious moments that everyone--introvert, extrovert, or somewhere in between--can relate to.